History of art the Western tradition - Janson, H. W. (Horst Woldemar) 1913-1982; Janson, Anthony F. (Pearson/Prentice-Hall, 2003)
Surveys the history of art in he western tradition, discussing the art of the ancient world, the Middle Ages, the Renaissance through the Rocco, and the modern world, and includes illustrations, time lines, and a glossary